Leadership Styles and Organizational Effectiveness: A Review of Recent Literature - Irianti, Irianti; Syarifuddin, Syarifuddin; Haerani, Andi (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study examines the relationship between leadership styles and organizational effectiveness by comprehensively reviewing recent literature. The aim is to provide insights into how different leadership approaches impact organizational outcomes. Research Design and Methodology: The research design involves a systematic review of recent literature on leadership styles and their effects on organizational effectiveness. Various databases were explored to identify relevant studies, and a rigorous screening process was employed to select articles that met the inclusion criteria. Findings and Discussion: The findings reveal that transformational leadership emerges as a critical determinant of organizational effectiveness, demonstrating a strong positive association with employee satisfaction, commitment, and overall performance. Transactional leadership is effective in stable environments but may hinder innovation in dynamic contexts. Servant leadership fosters a supportive work environment, positively impacting organizational citizenship behaviors and team performance. Adaptive and digital leadership styles are also gaining prominence, particularly in the face of technological advancements and changing market conditions. Implications: The findings highlight the importance of cultivating transformational leadership competencies within organizations to enhance organizational effectiveness. Investing in leadership development programs and fostering a culture that values visionary leadership can contribute to long-term success. Understanding the nuances of different leadership styles can help organizations adapt to evolving challenges and remain competitive in today's dynamic business landscape.